Ferns, frogs, lizards, birds and bats in forest fragments and shade cacao plantations in two contrasting landscapes in the Atlantic forest, Brazil - Faria, Deborah; Barradas Paciencia, Mateus Luis; Dixo, Marianna; Laps, Rudi Ricardo; Baumgarten, Julio (Springer, 2007)
The traditional shade cacao plantations (cabrucas) of southern Bahia, Brazil, are biologically rich habitats, encompassing many forest-dwelling species. However, a critical question for the conservation management of this specific region, and the highly fragmented Atlantic forest in general, is to what extent the conservation value of cabrucas relies on the presence of primary forest habitat in the landscape. We investigated the relative importance of cabrucas and forests for the conservation of five diverse biological groups (ferns, frogs, lizards, birds and bats) in two contrasting landscapes in southern Bahia, one dominated by forest with some interspersed cabrucas, and one dominated by cabrucas with interspersed forest fragments. The community structure (richness, abundance and diversity) of all biological groups differed between cabrucas and forests, although these differences varied among groups. A high number of forest species was found in the cabrucas. However, there were pronounced differences between the two landscapes with regard to the ability of cabrucas to maintain species richness. Irrespective of the biological group considered, cabrucas located in the landscape with few and small forest fragments supported impoverished assemblages compared to cabrucas located in the landscape with high forest cover. This suggests that a greater extent of native forest in the landscape positively influences the species richness of cabrucas. In the landscape with few small forest fragments interspersed into extensive areas of shade cacao plantations, the beta diversity of birds was higher than in the more forested landscape, suggesting that forest specialist species that rarely ventured into cabrucas were randomly lost from the fragments. These results stress both the importance and the vulnerability of the small forest patches remaining in landscapes dominated by shade plantations. They also point to the need to preserve sufficient areas of primary habitat even in landscapes where land use practices are generally favorable to the conservation of biodiversity.
Keywords: Atlantic forest; bats; birds; butterflies; babruca; ferns; frogs; landscape context; lizards; shade cacao plantation